Factors Influencing on Acceptance of Telehealth Service After Covid-19 Situation - Kaewbuadee, Saranchana; Kraiwanit, Tanpat (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
This research aims to examine factors in digital technology acceptance that affect decision-making for using telehealth services, decision-making models for using services, and the influence of factors in digital technology acceptance on telehealth service decision-making. The research included 400 Thai citizens aged 18 and above as participants. The research tool was to collect data by using online questionnaires. Which are divided into four parts: 1) demographic characteristics, 2) behavior of using telehealth services, 3) adoption of digital technology that affects to use telehealth services, and 4) service decision-making. The responses of 428 questionnaires were received and the remaining 400 samples were screened for accuracy. A questionnaire was used to describe by mean scores, standard deviation, Pearson’s product- moment correlation coefficients, and stepwise multiple regression analysis were used to analyze the data. The findings revealed that four factors in digital technology acceptance (usefulness, ease of use, safety, and the reliability of service providers) had a high-level mean. According to an analysis of the influence of factors in digital technology acceptance that affect the decision-making for using telehealth services, factors like usefulness, safety, and service providers’ reliability all influence the decision-making for using telehealth services at a significant level of 0.05 with an r-square of 0.224. When controlling for confounding factors, a one-point increase in the usefulness score led to a 0.237-point increase in decision-making, a one-point increase in the safety score resulted in a 0.167-point increase in decision-making, and an increase of one point in the reliability of service providers resulted in a 0.164-point increase in decision-making.